Negative emotion accumulation and personal motivation - Clément Staner (University of Heidelberg, Department of Economics, 2024)
Understanding how emotions stemming from negative outcomes affect investment decisions is critical for studying choice under uncertainty. I build a framework to study how past and anticipated negative emotions interact with an agent's preference and environment to influence her investment level. I show that the dynamic effect of emotions on decisions is more complicated than previously thought and requires a careful analysis of the decision environment to build correct predictions. Using baseball data, I show how to use the theoretical framework empirically to investigate the dynamic impact of emotion and find that it leads to suboptimal pitch velocity decisions.
urn:nbn:de:bsz:16-heidok-357737
Keywords: D90; D91; C13; 330; Emotion; Investitionsentscheidung unter Unsicherheit; Baseball; USA